PSIKOTERAPI ISLAM SHALAT TAHAJJUD DALAM MENINGKATKAN KESEHATAN MENTAL SANTRI - Abdur Rahman; Muhammad Ali Ma'sum (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
The purpose of this study is to describe emotional maturity, religiosity and aggressive behavior in the students of Pondok Pesantren Darussalam Blokagung Banyuwang using a qualitative method with a case study approach. The data collection techniques used are interviews, observation, documentation. The results of the research conducted through observation, interviews and documentation showed that the implementation of the tahajjud prayer in Islamic boarding schools showed a significant negative correlation between the regularity of praying and the level of anxiety. The more diligent and regular the santri perform the tahajjud prayer, the lower the level of anxiety and able to carry out all their activities